Analisis Laju Pertumbuhan Penduduk Terhadap Kemiskinan Provinsi Banten 2017-2019 - Deris Desmawan; Anne Fitrianovaline; Arastyo Djalal Latuconsina; Misha Nandenggan Siregar; Muhammad Noval Ramdani; Naufal Fauzan (Universitas Labuhanbatu, 2023)
Population growth and poverty rate are two important aspects of economic development that are interrelated. Population growth is an indicator that measures the level of people's welfare in a region, while poverty is a humanitarian problem that hinders the achievement of prosperity or prosperity. This study aims to analyze the growth rate of poverty in Banten province in 2017-2019. simple regression analysis was used by researchers in this study. The test results show that the population growth variable has a negative and insignificant effect on the poverty variable.